Colocaciones y captaciones de las instituciones financieras privadas de la ciudad de Loja durante la pandemia del COVID-19 periodo 2019 – 2020 - Ortega Romero, Graciela Elizabeth (2022)
The present research "Placements and acquisitions of private financial institutions in the city of Loja during the COVID-19 pandemic period 2019 – 202 0", seeks to estimate and analyze how this event determined the behavior of the portfolio of credits AND COLLECTIONS, the overdue portfolio and its influence on private banks; using a population made up of 12 private banks of the city of Loja, designed in a quantitative plane that allowed to collect, measure and analyze the data. The study methodology with a quantitative approach is analytical-descriptive, explanatory, documentary technique of information collection, and in the operational part sand made calculations, graphs and tables for the analysis of placements and collections, as well as the calculation of indicators such as: asset quality, administrative management, Profitability and Liquidity; the data were taken from the page of the Superintendency of Banks and Insurance of Ecuador. Among the first findings, it could be observed that both placements and acquisitions decreased proportionally compared to 2019, as a result of the pandemic in 2020; as regards the delinquency indicator, it shows a reduction in its percentage, this mainly due to the restructuring and extension of terms in the credits; the liquidity indicator reflected or instead an increase, this in front of the need of the banks to be able to comply with the cash requirements of their users; the indicators of administrative management also showed an increase, since it was necessary to increase the provisions of the banks to cope with a possible unproductive portfolio, finally the indicator that would be estimated affected, it is that of profitability, since the measures and actions taken by the banks in the face of the pandemic were largely to facilitate the situation of their debtors.